2018
DOI: 10.1111/acem.13508
|View full text |Cite
|
Sign up to set email alerts
|

Safety of the Combination of PERC and YEARS Rules in Patients With Low Clinical Probability of Pulmonary Embolism: A Retrospective Analysis of Two Large European Cohorts

Abstract: The combination of PERC then YEARS was associated with a low risk of PE diagnostic failure and would have resulted in a relative reduction of almost half of CTPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This particular CDM tool reduces the number of CTPA studies performed if the d-dimer is below a certain threshold and certain criteria are met ( Table 1). An interesting recent study demonstrated that if PERC was combined with YEARS, the failure rate was very low (0.57% failure rate), and resulted in a CTPA use reduction by 50%, as well as a reduction in d-dimer testing of 35% [21]. Although our study did not directly assess PERC utilization, the fact that we had 10 patients who were PERC negative and still had a CTPA study performed, is concerning for the underutilization of this validated CDM tool.…”
Section: Discussionmentioning
confidence: 99%
“…This particular CDM tool reduces the number of CTPA studies performed if the d-dimer is below a certain threshold and certain criteria are met ( Table 1). An interesting recent study demonstrated that if PERC was combined with YEARS, the failure rate was very low (0.57% failure rate), and resulted in a CTPA use reduction by 50%, as well as a reduction in d-dimer testing of 35% [21]. Although our study did not directly assess PERC utilization, the fact that we had 10 patients who were PERC negative and still had a CTPA study performed, is concerning for the underutilization of this validated CDM tool.…”
Section: Discussionmentioning
confidence: 99%
“…Combining these different strategies may be the more efficient way to reduce over-testing if it is proven to be safe. In a retrospective study involving 1951 patients who overall had a low probability (3.9% prevalence), combining the PERC rule and the YEARS rule made it possible to significantly reduce the number of CTAs, with a low rate of false negatives: 0.83% (95% CI = 0.51–1.35) [ 79 ]. Freund et al assessed this possibility in a cluster randomized cross-over trial in 18 ED [ 6 ].…”
Section: The Strategies Designed To Limit the Use Of Imaging Testsmentioning
confidence: 99%
“…The D-dimer threshold of 1,000 µg/L was used in cases of low clinical probability, while the classical threshold of 500 µg/L is used for moderate clinical probability, avoiding 16% of CTPA compared with the classical strategy and a failure rate of 0% (95% CI: 0-2.9%). 63 Recently, a new clinical probability score was derived. The 4PEPS merged all previous strategies with overtesting: ruling out PE on clinical criteria alone (PERC strategy), using 1,000 µg/L as the D-dimer cut-off in cases of low CP (PEGeD and YEARS strategy), using an age-adjusted D-dimer cut-off in cases of moderate CP (►Table 1).…”
Section: Strategies Against Overtestingmentioning
confidence: 99%